Watch this listen up : - Verklin, David (John Wiley & Sons, 2007)
In Watch This, Listen Up, Click Here, Verklin and Kanner expose the inner workings of the media, marketing, and advertising industries. Readers will learn why their favorite shows get cancelled, why Oprah gives away cars, and how money, people, politics, and new technologies are transforming TV, the Internet, radio, magazines, and other media Americans consume every day.